Family characteristics and health-related behaviours influence physical fighting involvement in late adolescence: a study from 13 to 17 years of age - Fraga, S (2016)
Aim: We aimed to assess the contribution of early characteristics in adolescence as associated factors of later involvement in physical fighting. Subject and methods: Based on data from a cohort of adolescents, we evaluated 1,687 participants, recruited in public and private schools in Porto, Portugal. Information on social and behavioural characteristics was collected using the same self-administered questions at 13 and 17 years of age. Logistic regression was used to estimate the magnitude of associations. Results: In both genders, physical fighting was significantly associated with living in a sole parent family, in particular only with the mother, and with early grade retention. Also, early cigarette smoking and alcohol drinking initiation were significantly associated with later involvement in fights. Conclusion: Our results show that family characteristics and modifiable behavioural trajectories are important determinants of later involvement in physical fighting.